2012
DOI: 10.5897/ajbm12.857
|View full text |Cite
|
Sign up to set email alerts
|

Psychology and behavior mechanism of micro-blog information spreading

Abstract: Micro-blog has a major influence on network information transmission of social emergency events for its incomparable qualities. The dissemination of micro-blog information has all the typical characteristics of compound transmission by internet and mobile communication network, which has gradually become the mainstream. In addition, the transmission process is more closely related to the psychology and behavior of each micro blogger. In this paper, we regard each micro-blog user as a different agent who dissem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…According to the diagram of the dissemination path of the microblog, it was found that the key users who disseminate information on social media on the use of wildlife are mainly environmental protection NGOs and popular science bloggers with considerable influence and a large number of followers. Opinion leaders, who often provide information on social media and effect the behavior and attitudes of others, play an imp0ortant intermediary role in achieving mass communication and are important promoters of public opinions (Hu 2012;Cai et al 2014). As the main opinion leaders in the field of wildlife protection, animal protection organizations become the guide for public sentiment on social media by increasingly mobilizing media through a variety of new media communication channels using values to gather public opinion and mobilize social resources, and enlisting influential third parties such as celebrities, well-known entrepreneurs and senior media professionals to make their views widely known (Huang and Zhun 2014).…”
Section: Dissemination Of Information On Wildlife Utilizationmentioning
confidence: 99%
“…According to the diagram of the dissemination path of the microblog, it was found that the key users who disseminate information on social media on the use of wildlife are mainly environmental protection NGOs and popular science bloggers with considerable influence and a large number of followers. Opinion leaders, who often provide information on social media and effect the behavior and attitudes of others, play an imp0ortant intermediary role in achieving mass communication and are important promoters of public opinions (Hu 2012;Cai et al 2014). As the main opinion leaders in the field of wildlife protection, animal protection organizations become the guide for public sentiment on social media by increasingly mobilizing media through a variety of new media communication channels using values to gather public opinion and mobilize social resources, and enlisting influential third parties such as celebrities, well-known entrepreneurs and senior media professionals to make their views widely known (Huang and Zhun 2014).…”
Section: Dissemination Of Information On Wildlife Utilizationmentioning
confidence: 99%
“…According to the diagram of the dissemination path of microblog, it is found that the key users who disseminate relevant information on the use of wildlife on social media are mainly environmental protection NGOs and popular science bloggers with greater in uence and a large number of fans. Opinion leaders who often provide information to others on social media and have the in uence to affect behavior and attitudes of others play an important intermediary role in the formation of achieving mass communication and are important promoters of forming many public opinions (Cai et al, 2014;Hu, 2012). As the main opinion leaders in the eld of wildlife protection, animal protection organizations become the guide of public opinion on social media by increasingly mobilizing media through a variety of new media communication channels, using values to gather public opinion and mobilize social resources, and seeking help from in uential third parties such as celebrities, well-known entrepreneurs and senior media professionals to make their views widely disseminated (Huang & Zhun, 2014).…”
Section: The Dissemination Of Relevant Information On Wildlife Utilizmentioning
confidence: 99%
“…In the past decades, numerous research works have been devoted to social networks [ 3 7 ]. Scholars conducted the technologies of content analysis and topic detection to study the information spread path as well as its key nodes [ 4 , 5 ] and furthermore probed into the topological structure and organizational mechanism of the spread network [ 6 – 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Scholars conducted the technologies of content analysis and topic detection to study the information spread path as well as its key nodes [ 4 , 5 ] and furthermore probed into the topological structure and organizational mechanism of the spread network [ 6 – 8 ]. It has been realized that information dissemination in social networks is affected not only by the variable network's structure and dynamically changing spread paths, but also by the complex interactive activities and group behaviors in social communities [ 7 , 8 ]. Therefore, statistical models such as time regression or estimators based on the traditional machine learning technologies are difficult to achieve good prediction results [ 6 , 9 ].…”
Section: Introductionmentioning
confidence: 99%